Indonesia di Era Susilo Bambang Yudhoyono (SBY) dan Joko Widodo: Kebijakan Luar Negeri di Tengah Dinamika Lingkungan [Indonesia under Susilo Bambang Yudhoyono (SBY) and Joko Widodo: Foreign Policy in the Middle of Regional Strategic Environment Dynamics] - Aji Widiatmaja; Ulul Albab (Jurnal Politica, 2019)
Indonesia’s foreign policy in the Susilo Bambang Yudhoyono’s (SBY) and Joko Widodo’s era have their own strengths and weaknesses. SBY's foreign policy tended to be outward-looking, which was marked by promotion of soft power, high politics, and leveraging Indonesia influence in global stage. Meanwhile, Joko Widodo's foreign policy is more inward-looking in that it focuses more on domestic sectors. Problems will arise if a country carries out its foreign policy in an unbalanced manner. Development in the global and regional strategic environment requires a collective response achieved in multilateral forums. This makes cooperation and active participation of a country in international forums become important. This paper aims to analyze Indonesia's foreign policy under SBY and Joko Widodo to find out the strengths and weaknesses of both foreign policies. The author has also provided a foreign policy recommendation that combines both inward and outward-looking perspectives in its performance. They are made in the form of reclaiming Indonesia's leadership in ASEAN to make the region a zone of peace, freedom, and neutrality (ZOPFAN), preventing foreign powers infiltration, maintaining ASEAN countries sovereignty, and curbing pragmatic and unilateralist actions in response to strategic environmental dynamics. These are important to ensure the achievement of Indonesia’s national interests. In simple terms, outward-looking policies are adopted as a tool to achieve national interests that benefit the Indonesian people (inward-looking).AbstrakKebijakan luar negeri Indonesia di era Susilo Bambang Yudhoyono (SBY) dan Joko Widodo memiliki kelebihan dan kekurangan masing-masing. Kebijakan luar negeri SBY cenderung outward looking dengan mengedepankan soft power dan bercorak high politics serta mencoba meningkatkan pengaruh Indonesia di forum global. Sedangkan kebijakan luar negeri Joko Widodo lebih bersifat inward looking yang berfokus pada penguatan sektor domestik. Permasalahan akan muncul jika suatu negara tidak berimbang dalam menjalankan kebijakan luar negerinya. Perkembangan lingkungan strategis global dan regional membutuhkan respon kolektif yang dicapai dalam forum-foum multilateral. Hal ini membuat kerjasama dan keaktifan suatu negara dalam forum internasional menjadi penting. Tulisan ini bertujuan untuk menganalisis kebijakan luar negeri Indonesia di era SBY dan Joko Widodo guna mengetahui kelebihan dan kekurangan masing-masing. Kemudian, penulis juga memberikan suatu rekomendasi kebijakan luar negeri yang menggabungkan corak inward dan outward looking dalam menjalankan kebijakan luar negeri. Hal tersebut berupa mengembalikan kepemimpinan Indonesia di ASEAN guna membuat ASEAN sebagai zone of peace, freedom, and neutrality (ZOPFAN), mencegah masuknya kekuatan asing, menajaga kedaulatan negara-negara ASEAN, serta mengurangi sikap pragmatis dan unilateralis dalam merespon perubahan lingkungan strategis. Hal tersebut penting dilakukan guna menjamin tercapainya kepentingan nasional Indoensia. Secara sederhana, kebijakan outward looking digunakan sebagai alat untuk mencapai kepentingan nasional yang memberi keuntungan pada rakyat Indonesia (inward looking).